PENGEMBANGAN MEDIA PEMBELAJARAN WEBSITE CHATBOT BERBASIS PEMECAHAN MASALAH PADA MATERI PENYAJIAN DATA UNTUK KELAS IV SEKOLAH DASAR - Fauziah, Anisa; Endang M. Kurnianti; Otib Satibi Hidayat (Universitas Nusantara PGRI Kediri, 2022)
This research was conducted to determine the feasibility of the learning media website chatbot based on problem-solving in present data for grade 4 elementary school at SDN Kapuk 05 Pagi. This study used research and development as the research method with four stages 4-D Thiagarajan development model, namely: 1) define, 2) design,3) develop, and 4) disseminate. The product of this research was a website chatbot learning media based on problem-solving in present data for grade IV elementary school. The feasibility level based on the results of the percentage assessment of material experts got 78%, learning media experts got 95.5%, linguists got 85%, the instructional design got 92%, one to one evaluation 90,9%, small group evaluation 84%, field test 82,1%, and teacher response assessment results produced was 93,75 %. Based on this result, it could be concluded that website chatbot learning media based on problem learning achieved the category of “very good” and